ANALISIS ASPEK KEJIWAAN TOKOH UTAMA NOVEL HATI SUHITA KARYA KHILMA ANIS (TINJAUAN PSIKOLOGI SASTRA - Nanda Maulana Hasmi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Literary work tries to describe human life, not only in relation to other humans, but also in relation to itself through the relationship of inner events. One form of literary work is novel. The birth of the novel is the creative result of the author in processing a story about life complete with various conflicts in it. Because this research is intended as a study of literary psychology to achieve the psychological aspects of the main character in the novel Hati Suhita by Khilma Anis, what will be put forward is the structure of the story which is closely related to the psychological exposure of the main character. The story structure is the characters and characterizations. As well as the story setting. Qualitative method. Namely, research procedures that produce qualitative descriptive data in the form of written or spoken words from people and observed behavior. How as much data as possible will be able to become the subject of research depends on the use of research techniques. While the approach is a literary assessment perspective. The approach is the scope of literary research. The form, content, and nature of literature as the subject of study. Until now, it seems that in literary research there is often confusion between the use of the terms method, technique and approach. As a result, there are overlapping areas of literary research. The method should involve the operational means of research. The method requires research steps that are worth following. The research results found by the researcher were in the form of the character of the main character and psychological conflicts in Khilma Anis' novel Hati Suhita. Suhita's character is good, tawadhu, smart. Al Birruni is firm, easy to change. Rengganis beautiful, smart. Aruna is good, cheerful. Kang Dharma is calm, mature. And the psychological conflict of Suhita's character is sad. Al Birruni didn't have the heart, Rengganis knew himself, Aruna was sad, and Kang Dharma was calm. In connection with conducting the research, the writer suggests that: first, literary reviewers are advised to examine more deeply the implicit and explicit values in Khilma Anis' novel Hati Suhita, because then we as readers can understand the author's message and his work in totality.